Education from a grassroots perspective - Ching, L.Y. (1983)
This paper examines the objectives of schooling as perceived by 540 Secondary school leavers, 60 teachers, 3 principals and. 60 parents of Kuala Langat district, Selangor in Peninsular Malaysia. School objectives, categorised as vocational preparation, self-development, social skills and Cultural understanding, and cultivation of interest are examined with reference to perceived importance and extent of success achieved.